Essentials of management - DuBrin, Andrew J. (Thomson South-Western, 2006)
Learn to apply the basic principles of management with Essentials of management! Using a functional approach, this management text gives you the tools you need to be successful in this course and in your career. See how management skills are applied in the workplace with features such as Manager in Action and Organization in Action that present a portrait of how specific individuals or organizations practice various aspects of management. Examples and activities found throughout help you develop the skills you need to manage, lead, and compete in today’s world.